Algorithmic game theory : 12th International Symposium, SAGT 2019, Athens, Greece, September 30-October 3, 2019, Proceedings /: 12th International Symposium, SAGT 2019, Athens, Greece, September 30-October 3, 2019, Proceedings. (2019) - Unknown
No abstract available